Analisis Tindakan Indisipliner Kerja Pada Pegawai PD.BPR Bank Gresik - Karima Diva Rifada; Maulidyah Amalina Rizqi (Universitas Muhammadiyah Gresik, 2021)
Background - Discipline is certainly an absolute requirement for the progress of the company or the progress of each individual. Without discipline, it would be impossible for all targets to be achieved properly, but at PD. BPR Bank Gresik there are employees who take disciplinary actions. Objective - To analyze the crimes committed by employees as well as the efforts made by PD. BPR Bank Gresik in improving employee discipline. Design/Methodology/Approach - This research is a type of qualitative research. Findings - The cause of disciplinary action information about weather conditions, interests, time scheduling and family conditions. The cause of disciplinary action by leaving early is unexpected conditions and needs for family needs, employees who do not use shoes when working hours are still ongoing due to weather conditions, healthy conditions, while employees who do not use ID cards are because employees think that the use of ID cards is only used when there is a meeting outside the office. Research implications - Research contributes to minimizing individual action. Research limitations - This research is expected to better prepare themselves in the process of retrieval, study data and everything else and further researchers are expected to be able to carry out deeper research with different methods related to Disciplinary Action.